PENGEMBANGAN SOAL HIGHER ORDER THINKING SKILLS PADA MATERI SISTEM GERAK KELAS XI SMA - Ana Wahyuni; Evi Suryawati; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning by using the 2013 curriculum emphasizes on higher-order thinking skills (HOTS). Students' higher-order thinking skills can be trained by providing evaluations in the form of HOTS test instrument. Learning in this digital era certainly must be able to utilize Information and Communication Technology (ICT) in the learning process. The process of constructing HOTS test instrument is based on multimedia by using iSpring Suite 9 software. This study aims to develop and to analyze high-quality multimedia-based Higher Order Thinking Skills (HOTS) test instrument about motion system materials for grade eleven senior high school students. This study was conducted at the Biology Education Study Program, Faculty of Teacher Training and Education, Universitas Riau, and SMAN Plus Riau Province Pekanbaru from November 2021 to March 2022. This research used the ADDIE model but only was done to the development stage. The result shows that the validation obtains an average score of 3.52 in the very valid category. The average response in the limited trial is 3.52 in the very good category. The average result of the quality of the HOTS test instrument for multimedia-based motion system materials is 3.52 in the very good category. Analysis of the items shows that the details of the items are reliable, 86.1% of the difficulty level of the HOTS items is in the difficult category, the discriminatory power 77.8% of the HOTS items is acceptable, 71.9% of the distractor function is effective. This study shows that the developed multimedia-based HOTS test instrument have a high quality so that they can be used as biology assessment instruments.Key Words: Multimedia, Motion Systems, Higher Order Thinking Skills (HOTS) test instrument.